ANALISIS PERBANDINGAN KEMUDAHAN BERINVESTASI TERHADAP OVERLAPPING REGULASI PENANAMAN MODAL ASING DI INDONESIA - Felicia Putri (2023)
Investment in Indonesia have begun to experience a significant increase from previous years, both from domestic investment and foreign investment. However, when compared to neighboring countries, Indonesia is still quite difficult for foreign investors to enter for various reasons. One of them is because there are overlapping regulations. So the author made this study with the aim of explaining the disharmonization of regulations that occur in Indonesia and comparing the openness of regulations related to foreign investment with Singapore and Malaysia. In this study, the author uses a normative juridical method with a comparative approach, a statutory approach and a conceptual approach. The data analysis technique used in this study is qualitative. In this study, the novelty produced by the author is related to the impact of regulatory overlapping that affects foreign investment activities in Indonesia and related to differences in regulations governing foreign investment activities in Indonesia, Singapore, and Malaysia. The author also provides an analysis related to the differences in ease of investing from the applicable regulations in Indonesia, Singapore, and Malaysia.